Green Care Farms: An Innovative Type of Adult Day Service to Stimulate Social Participation of People With Dementia. (9th October 2015) - de Bruin, Simone R.; Stoop, Annerieke; Molema, Claudia C. M.; Vaandrager, Lenneke; Hop, Peter J. W. M.; Baan, Caroline A.
Objective: To explore the value of day services at green care farms (GCFs) in terms of social participation for people with dementia.Method: Semi-structured interviews were conducted with people with dementia who attended day services at a GCF (GCF group, n = 21), were on a waiting list (WL) for day services at a GCF (WL group, n = 12), or attended day services in a regular day care facility (RDCF group, n = 17) and with their family caregivers.Results: People with dementia in the GCF and WL group were primarily males, with an average age of 71 and 76 years, respectively, who almost all had a spousal caregiver. People with dementia in the RDCF group were mostly females with an average age of 85 years, most of whom had a non-spousal caregiver. For both the GCF and RDCF groups, it was indicated that day services made people with dementia feel part of society. The most important domains of social participation addressed by RDCFs were social interactions and recreational activities. GCFs additionally addressed the domains "paid employment" and "volunteer work."Conclusion: GCFs are valuable in terms of social participation for a particular group of people with dementia. Matching characteristics of adult day services (ADS) centers to the preferences and capacities of people with dementia is of importance. Diversity in ADS centers is therefore desirable.